An "off–on" fluorescent probe for the detection of cysteine /homocysteine and its imaging in living cells. Issue 41 (11th April 2016) - Tang, Mengfang; Wu, Luling; Wu, Dan; Huang, Chusen; Zhu, Weiping; Xu, Yufang; Qian, Xuhong
Abstract : Based on the NCL reaction, we prepared an off/on fluorescent probeBQ for the selective sensing of Cys/Hcy. The discrimination of Cys and Hcy is achieved through the different rates of the transthioesterification reaction of Cys/Hcy withBQ . Abstract : Based on the NCL reaction, we report a novel "off–on" fluorescent probeBQ for the sensing of Cys/Hcy by a FRET strategy. Owing to the quenching effect of azo-based naphthalimide, BQ showed nonfluorescence. Upon the interaction of Cys/Hcy, a dramatic increase of the fluorescence signal was observed, with a high selectivity toward Cys/Hcy over GSH. Additionally, the discrimination of Cys from Hcy also could be achieved through the different rates of the transthioesterification reaction between thiols andBQ, especially when the concentration of Cys and Hcy was below 100 μM. The Cys/Hcy could be specifically labeled by the BODIPY fluorophore ofBQ after the NCL reaction. Living cell imaging experiments demonstrated thatBQ can selectively label Cys/Hcy and distinguish Cys/Hcy from other bioreagents including GSH in living systems.